Structural investigation of doubly-dehydrogenated pyrene cations. Issue 38 (30th July 2020) - Panchagnula, Sanjana; Bouwman, Jordy; Rap, Daniël B.; Castellanos, Pablo; Candian, Alessandra; Mackie, Cameron; Banhatti, Shreyak; Brünken, Sandra; Linnartz, Harold; Tielens, Alexander G. G. M.
Abstract : The first infrared predissociation spectra of the pyrene and doubly-dehydrogenated pyrene cations (C16 H10 ˙ + ; Py + and C16 H8 ˙ + ; ddPy + ) are presented. The vibrationally resolved spectrum of ddPy + is dominated by absorption features from two isomers. Abstract : The vibrationally resolved spectra of the pyrene cation and doubly-dehydrogenated pyrene cation (C16 H10 ˙ + ; Py + and C16 H8 ˙ + ; ddPy + ) are presented. Infrared predissociation spectroscopy is employed to measure the vibrational spectrum of both species using a cryogenically cooled 22-pole ion trap. The spectrum of Py + allows a detailed comparison with harmonic and anharmonic density functional theory (DFT) calculated normal mode frequencies. The spectrum of ddPy + is dominated by absorption features from two isomers (4, 5-ddPy + and 1, 2-ddPy + ) with, at most, minor contributions from other isomers. These findings can be extended to explore the release of hydrogen from interstellar PAH species. Our results suggest that this process favours the loss of adjacent hydrogen atoms.